PERSEPSI KARYAWAN KONTRAK DALAM MEMAHAMI KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA - Marheta, Venna Rosia; Sintyasari, Ita (Manajemen & Bisnis Jurnal, 2021)
The development of an increasingly globalized and competitive industry, many entrepreneurs apply a contract employee system, this is one of the tactics in facing global competition. Employees with legal contract status generally have a weak position in a company, if someone with contract employee status makes a mistake, their working relationship with an agency can be easily terminated without conditions. Every company must pay attention to the level of leadership ability in this case a manager in communicating properly and correctly to all employees so as to create a good family climate which can ultimately improve employee performance. Increasing effective and correct leadership is one aspect of the effectiveness of employee work. The dominant leadership role is very important, especially when it is associated with the necessity to interact with an ever-changing and evolving environment, partly because of the rapid advances in science and technology.